New evidence on state fiscal multipliers: Implications for state policies - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2017)
When state and local governments engage in balanced budget changes in taxes and spending, what fiscal multiplier effects do such policies have on creating local jobs? Traditionally, the view has been that possible job-creation effects of such state and local "demand-side" policies are smaller, second-order effects. Such effects might be worthwhile to take into consideration when a state or local government balances its budget during a recession, but the effects were believed to be of modest magnitude, and not of major importance for more general state and local public policies. However, recent estimates of fiscal multiplier effects of state and local spending and tax policies suggest much larger demand-side effects of such policies on local jobs. These fiscal multiplier effects are large enough to suggest relatively low costs per job created of some tax and spending policy combinations, sufficient to alter the net benefits of many public policies. In particular, this recent research suggests that policies that use tax increases on the top 10 percent of the income distribution to finance either public spending expansions or tax relief for the bottom 90 percent of the income distribution may offer some job creation benefits that are large enough to alter state and local policy decisions. Furthermore, the cost per job created of state business tax incentive policies or business tax cuts may be significantly altered after taking into account the opportunity costs of financing such policies by cutting public spending or raising taxes on the bottom 90 percent.
Keywords: H71; H72; J23; R12; 330; job creation; fiscal multipliers; state and local taxation; state and local expenditures; local labor demand; income distribution; business tax incentives; state and local business taxes